2010
DOI: 10.1002/jobm.201000065
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of native rhizobia trapped by five field pea genotypes in Indian soils

Abstract: Five pea cultivars; HFP 4, HVP 3-5, HFP 9426, Jayanti and Hariyal, being grown in CCS Haryana Agricultural University farm were used to isolate native rhizobia. Selected 54 rhizobia, from all cultivars, were authenticated as rhizobia by plant infectivity test. Along with nodulation, symbiotic effectiveness in terms of symbiotic ratios showed wide range of effectiveness of pea rhizobia from 1.11 to 5.0. DNA of all the 54 rhizobia was extracted and amplified by PCR, using ERIC and 16S rDNA primers. Dendrogram ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…To isolate endophytes the roots and nodules were surface sterilized by using 0.2% mercuric chloride and ethanol and then rinsed with sterile water four to six times . Roots were crushed for isolation of endophytes whereas a cut was made in the nodules with a sterilized knife and then a loop ful of root and nodule sap was streaked on separate Tryptone Soya Agar (TSA) medium plates . The plates were incubated at 28 ± 2 °C for 5–6 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To isolate endophytes the roots and nodules were surface sterilized by using 0.2% mercuric chloride and ethanol and then rinsed with sterile water four to six times . Roots were crushed for isolation of endophytes whereas a cut was made in the nodules with a sterilized knife and then a loop ful of root and nodule sap was streaked on separate Tryptone Soya Agar (TSA) medium plates . The plates were incubated at 28 ± 2 °C for 5–6 days.…”
Section: Methodsmentioning
confidence: 99%
“…Further all the endophytic isolates were inoculated separately in Tryptone soya broth and incubated on rotary shaker at 28 ± 2 °C. Germinated chickpea seedlings of variety HC5 were transferred to sterilized cups containing sand as detailed earlier . Seedlings were inoculated with 1–2 ml broth of Mesorhizobium sp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ancestral lifestyle of rhizobia was probably rhizospheric, and the degradative capabilities of rhizospheric bacteria have been highlighted [3]. It is well known that crop plants belonging to the genera Vicia, Lathyrus, Pisum and Lens are effectively nodulated by isolates of Rhizobium leguminosarum biovar viciae [4]. The symbiotic interaction between rhizobia and legumes is initiated by an exchange of complex molecular signals that confer host-specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Subgroup II was having only one isolate (BH44) which further showed that this isolate is different from all the other members of major group I. Isolates BH13 and BH52 showed 100% similarity among themselves and the same was observed for BH36 and BK81; BS12, BK76 and BK51; BS14 and BH16. However, it was observed that 100% similarity was not shown by rhizobia isolated from nodules of the same plants as also reported by Wadhwa et al, (2011). Similarly, large number of groups and further subgroups of rhizobia infecting different legumes have been reported in different parts of the world, revealing considerable molecular diversity (Nandwani and Dudeja, 2009;De Meyer et al, 2011;Choudhary et al, 2013 Table 2.…”
Section: Resultsmentioning
confidence: 61%